2017
DOI: 10.3390/nu9090999
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng Leaf Extracts Exert Anti-Obesity Effects in High-Fat Diet-Induced Obese Rats

Abstract: Recent studies have reported that the aerial parts of ginseng contain various saponins, which have anti-oxidative, anti-inflammatory, and anti-obesity properties similar to those of ginseng root. However, the leaf extracts of Korean ginseng have not yet been investigated. In this study, we demonstrate the anti-obesity effects of green leaf and dried leaf extracts (GL and DL, respectively) of ginseng in high-fat diet (HFD)-induced obese rats. The administration of GL and DL to HFD-induced obese rats significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
(25 reference statements)
0
21
0
Order By: Relevance
“…In Zucker obese rats, Nopal consumption attenuated hepatic steatosis related to obesity and reduced obesity-related metabolic abnormalities. Vinegar or isolated molecules present in Opuntia cladodes, such as kaempferol or isorhamnetin, used in obese mice models, corroborated the anti-obesity and anti-diabetic potentials of these molecules [15][16][17][18][19][20][21]. These studies suggest that remarkable effects could be observed in rat/mouse models of obesity induced by a high-fat diet (HFD), supplemented with Opuntia cladode powders (OCP).…”
Section: Introductionmentioning
confidence: 76%
“…In Zucker obese rats, Nopal consumption attenuated hepatic steatosis related to obesity and reduced obesity-related metabolic abnormalities. Vinegar or isolated molecules present in Opuntia cladodes, such as kaempferol or isorhamnetin, used in obese mice models, corroborated the anti-obesity and anti-diabetic potentials of these molecules [15][16][17][18][19][20][21]. These studies suggest that remarkable effects could be observed in rat/mouse models of obesity induced by a high-fat diet (HFD), supplemented with Opuntia cladode powders (OCP).…”
Section: Introductionmentioning
confidence: 76%
“…The underlying cause of obesity can be attributed to the diet, genetic disorders, sedentary lifestyle, and psychological factors. The imbalance between energy intake and expenditure also causes the buildup of excess adipose tissue [2].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is characterized by chronic energy imbalance, excessive body weight, white adipose tissue (WAT) and lipogenesis [1,2,41] In addition, obesity is associated with increased oxidative stress and inflammation. Therefore, the functions of antioxidants in the body cannot be overemphasized.…”
Section: Antioxidant Properties Of Selected Seaweed Carotenoidsmentioning
confidence: 99%